Quickness and endurance fitness of pedagogic college girl students under influence of cheer-leading - I.P. Masliak (Physical Education of Students, 2015)
Purpose: to determine dynamic of quickness and endurance indicators of pedagogic college girl students under influence of cheer-leading. Material: in the research 385 girl students participated, who composed three control and three experimental groups. Quickness fitness was registered by indicators of 60 meters’ run (sec.); latent time of motor response (msec.); run on the sport during 5 sec (quantity of steps); tapping test (quantity of points). Level of endurance fitness was registered by results of 2000 meters’ run (min). Results: the most effective cheer-leading exercises, which positively influence on girl students’ endurance, have been determined. The most favorable age periods for training of quickness and endurance under influence of cheer-leading exercises have been found. The higher increment in quickness indicators was registered in 15 years old girls. The most substantial increment of endurance was registered in 16 years old girls. Conclusions: it is recommended to include cheer-leading exercises: basic movements, jump elements, constants, in variable components of girl students’ academic training program.